2019
DOI: 10.1002/cbin.11152
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA TUSC8 inhibits the invasion and migration of cervical cancer cells via miR‐641/PTEN axis

Abstract: Cervical cancer (CC) is the fourth leading cause of cancer‐related death in women worldwide. There is an urgent need to find novel targets for the treatment of CC. Recently, microRNA have emerged as critical factors in tumorigenesis. In this study, we aimed to investigate the mechanism of miR‐641 on the migration and invasion of CC cells. In silico analysis revealed putative interaction between miR‐641 and phosphatase and tensin homolog (PTEN) RNA/lncRNA tumor suppressor candidate 8 (TUSC8). Hence we evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 23 publications
(24 reference statements)
3
21
0
Order By: Relevance
“…lncRNA RP4 suppresses the development of colorectal cancer by acting as a sponge for miR-7-5p (8). It is worth noting that TUSc8 plays an anti-oncogenic role in cervical cancer by sponging miR-641 (14). Moreover, a recent study indicated that TUSc8 functions as a ceRNA of MYLIP by competitively binding with miR-190b-5p to inhibit breast cancer growth (36).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…lncRNA RP4 suppresses the development of colorectal cancer by acting as a sponge for miR-7-5p (8). It is worth noting that TUSc8 plays an anti-oncogenic role in cervical cancer by sponging miR-641 (14). Moreover, a recent study indicated that TUSc8 functions as a ceRNA of MYLIP by competitively binding with miR-190b-5p to inhibit breast cancer growth (36).…”
Section: Discussionmentioning
confidence: 99%
“…TUG1 knockdown also suppresses OS cell proliferation and invasion via miR-153 (13). Indeed, recent evidence has revealed that TUSc8 serves as a tumour suppressor in the development of cervical cancer by regulating the miR-641/PTEN pathway (14). However, as a novel lncRNA, the specific role of TUSC8 in OS has not yet been clarified.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, lncRNA, as a ceRNA, plays an important role in the development of cervical cancer by sponging miRNA to regulate expression of genes. For example, lncRNA TUSC8 can upregulate the expression of PTEN by sponging miR-641, thereby inhibiting the invasion and migration of cervical cancer cells [31]. LncRNA MIR205HG can act as a ceRNA to promote the proliferation and migration of cervical cancer cells by reversing the inhibitory effect of miR-122-5p on FOXP2 [32].…”
Section: Discussionmentioning
confidence: 99%
“…According to previous studies, several lncRNAs have been reported to be involved in the progression of CC. lncRNA TUSC8 plays an important role in inhibiting the invasion and migration of CC cells via miR-641/PTEN axis (9). lncRNA MIR205HG acts as a competing endogenous RNA (ceRNA) and modulates tumor growth and progression via sponging miR-122-5p in CC (10).…”
Section: Introductionmentioning
confidence: 99%